Effects of low ambient temperatures and dietary vitamin C supplementation on pulmonary vascular remodeling and hypoxic gene expression of 21-d-old broilers - Qiu-feng ZENG; Xia YANG; Ping ZHENG; Ke-ying ZHANG; Yu-heng LUO; Xue-mei DING; Shi-ping BAI; Jian-ping WANG; Yue XUAN; Zhuo-wei SU (Journal of Integrative Agriculture, 2016)
The objective of this study was to evaluate the effects of low ambient temperature (LAT) and dietary vitamin C (VC) supplementation on pulmonary vascular remodeling (PVR) and the relative expression of hypoxia inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF) and its receptor 2 (VEGFR-2) mRNA of lungs in 21-d-old broilers. 400 1-d-old male Cobb broilers were assigned randomly to 4 treatments as follows for 21 d: 1) LAT and a basal diet; 2) LAT and a basal diet supplemented with 1 000 mg kg−1 VC (LAT+VC); 3) normal ambient temperature (NAT) and a basal diet; 4) NAT and a basal diet supplemented with 1 000 mg kg−1 VC (NAT+VC). Each treatment was composed of 10 replicates of 10 birds per replicate. Samples of lung were collected after the broilers were killed at d 21. LAT increased the ratio of vessel wall area to vessel total area (WA/TA, %) and mean media thickness in pulmonary arterioles (mMTPA, %) (P<0.05). Dietary VC supplementation decreased mMTPA (P<0.05), but had no effect on the WA/TA. LAT increased (P<0.05) the relative mRNA expression of HIF-1α, VEGF and VEGFR-2, while adding VC to the diet could decrease (P<0.05) their relative mRNA expression. A significant positive correlation existed between the level of VEGF mRNA expression and the value of WA/WT (P<0.05) or mMTPA (P<0.05). These results suggested LAT resulted in pulmonary vascular remodeling, and the increase of HIF-1α, VEGF and VEGFR-2 mRNA expression, and dietary VC supplementation can alleviate pulmonary vascular remodeling in broiler by affecting these gene expression.